(untitled) - Kiev, Ari (Hoboken, N.J., 2008)
In Mastering Trading Stress, author Ari Kiev—a psychiatrist who specializes in stress management and works extensively with traders—offers examples, transcripts of conversations, and personality profiles of real-life traders to illustrate how stress affects their ability to perform at their best. Drawing on his vast experience, Kiev describes a variety of practical techniques that can be used to handle destructive emotions and out-of-control feelings, including his “Most Basic” stress busters, and tells what to do if a breakdown should occur.
Keywords: Investments,Speculation,Đầu tư,Đầu cơ; Psychological aspects,Psychological aspects,Khía cạnh tâm lý,Khía cạnh tâm lý